Cognitive therapy for depression: theoretical reflection and personal thinkings - Beck, Aaron Temkin (Psyhology & society, 2019)
Cognitive therapy did not emerge full-blown but went through many researches before it reached its present form. A. Beck’s ﬁrst foray into the area of cognition actually occurred as a result of an interaction with depressive patients while practicing psychoanalysis and psychodynamic psychotherapy. When the researcher ﬁtted together the observations of the reported automatic thoughts of these patients and his own introspective explorations, he started to arrive at the beginnings of a cognitive theory and the existence of two systems of thoughts. One system is directed to others and, when freely expressed, consists of the kinds of feelings and thoughts that one commonly communicates to other people. This form of thinking and communicating constitutes “the conversational mode” of thinking, or “the mode of dialogue”. The second system of thoughts is “the self-signalling mode”. It consists of self-monitoring, self-instructions, and self-warnings. It also includes rapid, automatic interpretation of events, self-evaluations, and anticipations. Its function is communication with oneself rather than with other people. The researcher discovered, the internal communication system was the source of much of the patients' problems and by tapping into it we could better understand the patients' difﬁculties and help them to resolve them.The negativity of depression as a psychological state permeated the patients' internal communications, such as self-evaluation, attributions, expectancies, inferences, and recall, and was manifested in low self-esteem, self-blame and self-criticism, negative predictions, negative interpretations of experiences, and unpleasant recollections. A. Beck observed that the depressed patients were particularly prone to make a negative interpretation when a positive one would seem to be more appropriate. Furthermore, they would not only magnify their own unpleasant experiences but would either blot out their experiences that other people would consider positive. In particular, in the course of investigations it was noted that depressed patients tended to predict speciﬁc negative outcomes from tasks that they might undertake and expected long-range, bad outcomes to their life in general. A high degree of such negative expectations (“hopelessness”) appeared to be predictive of suicide. These phenomena appeared to be universal across all types of sub-types of depression, irrespective of whether the primary diagnosis was depression, schizophrenia, or some other disorder. As the depressed patients were ﬁlled with covert hostility, the dreams would be a place where this hostility could be identiﬁed. It has been proved that the depressed patients showed less hostility in their dreams than did the non-depressed patients. Although the depressed patients had fewer dreams in which they played an aggressive or hostile role, they were the victim of some unpleasant event: they were thwarted, deprived, disappointed and depreciated.By suffering, they would be punishing themselves; that is, inﬂicting the hostility against themselves. This "masochism" would be manifested in their self-criticism, courting rejection and suicidal desires. All of the depressed patients had more masochistic dreams than did any of the non-depressed patients. Thus, the preliminary conﬁrmation of the psychoanalytic theory of depression must be both enriched hypothetically by a variety of vantage points and by using differing techniques and psychotherapeutic practice protocol.